Downregulation of GRK6 in arcuate nucleus promotes chronic visceral hypersensitivity via NF-κB upregulation in adult rats with neonatal maternal deprivation. (May 2020) - Li, Xin; Xu, Yu-Cheng; Tian, Yuan-Qin; Zhang, Ping-An; Hu, Shu-Fen; Wang, Lin-Hui; Jiang, Xing-Hong; Xu, Guang-Yin
Aims: The arcuate nucleus is a vital brain region for coursing of pain command. G protein-coupled kinase 6 (GRK6) accommodates signaling through G protein-coupled receptors. Studies have demonstrated that GRK6 is involved in inflammatory pain and neuropathic pain. The present study was designed to explore the role and the underlying mechanism of GRK6 in arcuate nucleus of chronic visceral pain. Methods: Chronic visceral pain of rats was induced by neonatal maternal deprivation and evaluated by monitoring the threshold of colorectal distension. Western blotting, immunofluorescence, real-time quantitative polymerase chain reaction techniques, and Nissl staining were employed to determine the expression and mutual effect of GRK6 with nuclear factor κB (NF-κB). Results: Expression of GRK6 in arcuate nucleus was significantly reduced in neonatal maternal deprivation rats when compared with control rats. GRK6 was mainly expressed in arcuate nucleus neurons, but not in astrocytes, and a little in microglial cells. Neonatal maternal deprivation reduced the percentage of GRK6-positive neurons of arcuate nucleus. Overexpression of GRK6 by Lentiviral injection into arcuate nucleus reversed chronic visceral pain in neonatal maternal deprivation rats. Furthermore, the expression of NF-κB in arcuate nucleus was markedly upregulated in neonatal maternal deprivation rats. NF-κB selective inhibitor pyrrolidine dithiocarbamate suppressed chronic visceral pain in neonatal maternal deprivation rats. GRK6 and NF-κB were expressed in the arcuate nucleus neurons. Importantly, overexpression of GRK6 reversed NF-κB expression at the protein level. In contrast, injection of pyrrolidine dithiocarbamate once daily for seven consecutive days did not alter GRK6 expression in arcuate nucleus of neonatal maternal deprivation rats. Conclusions: Present data suggest that GRK6 might be a pivotal molecule participated in the central mechanisms of chronic visceral pain, which might be mediated by inhibiting NF-κB signal pathway. Overexpression of GRK6 possibly represents a potential strategy for therapy of chronic visceral pain.